Clarion Call for Africa to meet at the Middle in the Malaria Vaccine Introduction - Global Communications Director (My University, 2020)
Malaria still, severely, impacts life and health in Africa and remains one of the continent’s biggest killers. It is estimated that four out of 10 pregnant women are exposed to the malaria parasite, leading to maternal deaths, underweight children, and potential lifelong disabilities. These may have contributed to the death of more than 250,000 children under the age of five in Africa in 2019. Households sink deeper into poverty as they deal with increased out-of-pocket expenditures in accessing care and treatment. Additionally, modelling studies have shown that COVID-19-related disruptions in access to effective antimalarial treatment are likely to reverse all progress made in reducing morbidity and malarial deaths in Africa.
Keywords: malaria vaccine; Mosquirix; morbidity and malarial deaths in Africa